Settlement of Customary Law Community Land Disputes Regarding the Construction of the Lukas Enembe Stadium in Kampung Harapan Jayapura Regency - James Yoseph Palenewen; Tom Alfa Samuel Reumi (Journal of Law, Politic and Humanities, 2024)
Land disputes often occur in rural and urban areas, as is the case with customary land disputes between the traditional law community of Harapan Village and the Papua Provincial Government on whose land the Lukas Enembe Stadium was built in Harapan Village. The aim of this research is to determine the responsibility of the Papua Provincial Government towards the ulayat land of the traditional law community of Harapan village where the Lukas Enembe Stadium has been built and also how to resolve the ulayat land dispute by both parties. The results of this research reveal that the responsibility of the Papua Provincial Government in resolving customary land disputes in Kampung Harapan is that the Papua Provincial Government basically submits to court decisions which have permanent legal force, so that all compensation payments for Kampung Harapan's customary land will be directed only to the Plaintiff. The person who won the case in this case was the heir of Plaintiff I, Agustinus Ph Ohee, and the heir of Plaintiff II, Eliab Ongge, S.Ip, MM. and resolving customary land disputes between Harapan village and the Papua Provincial Government, namely through a very long process, either through litigation (court) or non-litigation (outside court), namely through court decisions, through state administration decisions (PTUN) and through customary law decisions. . All these steps were taken to prove who really has the right to the 62 ha (sixty two hectares) ulayat land of Harapan village.